The phytochemicals and health benefits of Cyclocarya paliurus (Batalin) Iljinskaja - Shen, Yingbin; Peng, Yao; Zhu, Xucheng; Li, Haimei; Zhang, Liwen; Kong, Fanlei; Wang, Jia; Yu, Di (Frontiers in Nutrition, 2023)
Cyclocarya paliurus (C. paliurus), a nutritional and nutraceutical resource for human and animal diets, has been constantly explored. The available biological components of C. paliurus were triterpenoids, polysaccharides, and flavonoids. Recent studies in phytochemical-phytochemistry; pharmacological-pharmacology has shown that C. paliurus performed medicinal value, such as antihypertensive, antioxidant, anticancer, antimicrobial, anti-inflammatory and immunological activities. Furthermore, C. paliurus and its extracts added to drinks would help to prevent and mitigate chronic diseases. This review provides an overview of the nutritional composition and functional applications of C. paliurus, summarizing the research progress on the extraction methods, structural characteristics, and biological activities. Therefore, it may be a promising candidate for developing functional ingredients in traditional Chinese medicine. However, a more profound understanding of its active compounds and active mechanisms through which they perform biological activities is required. As a result, the plant needs further investigation in vitro and in vivo.